The age and depositional environments of the lower Karoo Moatize Coalfield of Mozambique: insights into the postglacial history of central Gondwana - Fernandes, Paulo (2024)
The Moatize Coalfield belongs to a network of continental Karoo basins of central Mozambique, known as the Zambezi Basin. Palynological and sedimentological studies were performed on four coal exploration boreholes to determine the age, depositional settings, and overall geological evolution of its extensive coal deposits. Clastic formations recognised in this coalfield, in ascending order, are the Vu´zi, Moatize and Matinde formations. Palynomorph assemblages indicate that the Moatize Coalfield succession ranges from Roadian (lower Guadalupian) to Changhsingian (upper Lopingian) in age. Two main depositional phases are identified, whose initiation and development are attributed to regional tectonic events and climate amelioration. The first phase formed towards the end of the deglacial period, characterised initially by fan deltas, represented by the upper Vu´zi Formation, and the shift to lake–delta environments, represented by the lower part of the Moatize Formation. This phase took place from Roadian to the Wordian times. The lake–delta settings indicate a sediment aggradation trend with high subsidence rates in the lake basin, which, together with the associated post-glacial climate amelioration, led to the accumulation of coal deposits in swamps of the delta top and lake margins. The second depositional phase took place from Capitanian to Changhsingian times and related to fluvial environments initiated by uplift that reorganised the depocenter into alluvial plains characterised by bedload dominated rivers (braided) and overbank floodplains. Results obtained in this study provide critical information for the onset of the deglaciation events and the age of coal deposits in this part of Gondwana, important for wider stratigraphic correlation of these events in Africa and throughout the Gondwana.